Social Studies Learning Motivation of Fourth Grade Students at Al-Munawwarah Private Elementary School Jambi City - Rizna Syahputri; Shalahudin; Sean Popo Hardi (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This research discusses the learning motivation of fourth-grade students in IPAS learning at Al-Munawwarah Private Islamic Elementary School, Jambi City. The study focused on students’ learning motivation, the factors influencing it, and the teacher’s strategies to improve students’ motivation during classroom learning activities. A descriptive qualitative approach was applied using observation, interviews, and documentation as data collection techniques. The findings revealed that students’ learning motivation showed different conditions. Some students were active and enthusiastic during learning activities, while others were still less confident and less involved in classroom learning. Both internal and external factors influenced students’ learning motivation. In addition, the use of varied learning methods, learning motivation from teachers, and interesting learning media helped improve students’ enthusiasm in IPAS learning.